Development of Three-Dimensional Non-Contact Surface Profilometer and Application to Evaluation of Impact Erosion of Metal Matrix Composites - Yoshiro Iwai (Japanese Society of Tribologists, 2008)
A three dimensional non-contact surface profilometer system which can measure a wide area (order of square milli-meters) with high resolution (sub micro meter) has been completed. This system can measure the surface topography in the atmosphere by means of a confocal wavelength displacement sensor. We examined the optimum measurement conditions and applied them to the evaluation of erosion properties of particle reinforced metal composites. As a result, a scanning speed of 1mm/s and sampling intervals of 0.5-15μm were found to the optimum conditions. In addition, we evaluated the differences of properties in composite materials with different volume fractions using this system. We conclude that our technique is useful in the evaluation of erosion properties of composite materials.